来华留学生汉语学习动机特点及其个体差异性研究 - Yue Jiang; Yijie Wang; Shuang Zhang (Journal of Maobi, 2025)
This paper explores the characteristics of Chinese language learning motivation and its individual differences among 147 international students enrolled in a Chinese language program at a local university in central China by using quantitative survey method. Descriptive analysis and Independent sample T-test were conducted on the collected data through SPSS27.0. The research results showed that 1) the Chinese language learning motivation of international students in China was at a high level overall, 2) there were no significant differences in relation to gender in the participants’ Chinese language learning motivation; the participants were significantly different in ought-to L2 self and L2 learning experience in relation to age; the participants with difference Chinese language proficiency were significantly different in ought-to L2 self. Based on these results, Chinese teaching should adopt differentiated teaching strategies to fully meet the diverse needs of international Chinese language learners and thus improve the pertinence and effectiveness of Chinese language teaching.